Concerns and needs of parents of hospitalized children - Rodrigues, Joana Isabel Barbosa; Fernandes, Susana Margarida Gonçalves Caires; Marques, Goreti Filipa dos Santos (Saúde e Sociedade, 2020)
Pediatric hospitalization is a critical event with repercussions on the life of hospitalized children and their families. This study recorded the main concerns and needs experienced by parents during the hospitalization of a child under acute hospitalization, and verified the potential differences between the father and the mother regarding their shared experiences. This qualitative study of exploratory nature involved 16 couples (16 fathers and 16 mothers), with a child hospitalized in a pediatric service of a hospital in the north of Portugal. The data were collected through interviews and analyzed using content analysis. The parents’ discourse shows significantly more concern regarding the state of health of the child as well as their recovery and homecoming, among the most urgent needs. The results showed presence of significant differences in the experiences of these couples, not only due to the father/mother variable, but also due to their central role regarding child care (primary or secondary caregiver).